Potential Plant Secondary Metabolites for the Prevention of Skin Cancers and their Mechanism: A Review - Kadian, Jai P.; Kaushik, Madan Lal; Chauhan, Bhupendra; Singh, Aniruddh Dev (Current Traditional Medicine, 2023)
Skin carcinoma is the most common malignancy, including malignant melanoma and non-malignant melanoma throughout the world, and in the last three decades, its incidences have been increasing drastically. High cost, severe side effects and development of resistance from conventional chemotherapy have decreased its acceptability and increased the urge for the search for alternate options. Therefore, plant derived phytochemicals have come up with cost effectiveness, ease of availability and promising potential for skin related cancers. In spite of the lack of clinical data involving humans to support the positive effects of phytochemicals on different types of skin cancers, topical application of these plant derived anticancer phytochemicals is extremely promising. Many mechanisms and pathways underlie the antitumor activity of plant-derived phytochemicals , such as loss of mitochondrial membrane potential, the release of cytochrome-c, suppression of antiapoptotic proteins and induction of proapoptotic proteins, activation of caspases, Fas, FADD and p53 signaling pathway, inhibition of Akt signaling pathway, phosphorylation of ERK, P13K, Raf, survivin gene, STAT 3 and NF-kB. The use of cell line models in the in vitro study of skin cancer offers the opportunity to identify the mechanisms of action of plant derived phytochemicals against various types of skin cancer. As such, this article aims at providing a comprehensive review of plant extracts and phytochemicals, which have been reported to exhibit promising anti-carcinogenic properties in animal models and against various skin cancer cell lines.
Keywords: metabolites